Analisis Efisiensi Mesin Produksi Forming Machine Pada Cv. Agrindo Supra Food Menggunakan Metode OEE - Dedi Setiawan; Ari Zaqi Al-Faritsy (JURNAL ILMIAH RESEARCH STUDENT, 2026)
CV. Agrindo Supra Food is an agro-industrial company located in Bantul, Yogyakarta, specializing in nata de coco production. The main issue identified is the suboptimal performance of the Forming Machine, with breakdowns occurring up to five times per week, each requiring an average repair time of 30–45 minutes. Setup processes often take twice as long as the ideal 10 minutes, and defective products during startup account for 8–12% of daily output. These problems stem from the absence of a routine maintenance schedule, inefficient equipment layout, and insufficient operator understanding of process parameters. To evaluate machine performance, the Overall Equipment Effectiveness (OEE) method was applied, covering three key indicators: Availability, Performance, and Quality. Loss analysis was conducted using the Six Big Losses approach. The results showed an Availability of 65.5%, Performance of 88.2%, and Quality of 77.6%, with a total OEE score of only 44.7%, far below the world-class standard of 85%. Improvement strategies include scheduled maintenance, operator training, and standardized work procedures.